Use of multispectral satellite imagery to monitor erosion on the Volyn Upland. - Fedoniuk, M.; Kovalchuk, I.; Zhdaniuk, Bohdan S.; Fedoniuk, V.; Pavlovska, Tetiana S. (European Association of Geoscientists & Engineers, 2020)
The paper presents an overview of how dynamics changes of erosive landforms of the Volyn Upland (North-Western Ukraine) can be evaluated. For this, the satellite imagery by Google Earth, EOS Landviewer, and Sentinel-2 is used. The research provides examples of how ravines are represented on images with different spectral ranges. There are significant differences in remote identification of erosion forms for forested areas, cultivated and uncultivated lands. For each of these types, the images from different spectral channels during both growing and non-growing periods are analyzed. The results are presented in a table: it shows informative and practical value of different channels and indexes to detect and evaluate the dynamics of erosion landforms. Visible and near-infrared channels are found to be the most informative. Combining vegetation index, moisture index, and thermal infrared channel proved to be less informative. It is possible to extract some additional information through them though. The paper also provides suggestions on the use of remote sensing for erosion monitoring.
Keywords: erosive landforms; Volyn Upland; satellite images; remote sensing of the Earth